Venture Builders and the Creation of Scaleups De-Risking Entrepreneurship to Drive High-Growth Companies - Belingheri, Paola; Lechner, Christian; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This open access book explores the phenomenon of venture builders as an emerging startup support model for creating startups. Unlike traditional accelerators or incubators, venture builders intervene from the startups$1 (Binception, leveraging structured processes and expert guidance to mitigate risks and accelerate startups. The authors present a novel classification of venture building models and assess their effectiveness in fostering scaleups$1 (Bhigh-growth firms vital to innovation and economic growth. Using original interview data and datasets on European venture builders$1 (Bambitions, the authors identify key design archetypes and examine how resource access, funding, and de-risking influence the potential to create rapidly scaling startups. By linking practice with research, the book offers actionable insights for policymakers, academics, and practitioners. Whether you are a manager in a venture builder, a policymaker aiming to stimulate growth, or a researcher studying entrepreneurship, this book will illuminate how venture builders can unlock new opportunities in high-growth entrepreneurship. Paola Belingheri is a Lecturer in Entrepreneurship and Innovation at Luiss University in Rome. She co-founded several startups and has experienced a host of incubation and acceleration programs. Her research includes studies on technology entrepreneurship through licensing, how entrepreneurs approach patenting, and the potential of venture building to foster scaleups. Christian Lechner is Professor of Entrepreneurship and Director of the Department in Business & Management at Luiss University, Rome. He has been advising startups, launched the TBSeeds incubator of Toulouse Business School, built programs across Europe, and published widely in top journals, contributing to research, policy, and entrepreneurial ecosystem development.s
Chapter 1: Introduction -- Chapter 2: Transitioning from Startups to Scaleups -- Chapter 3: The Venture Building Phenomenon -- Chapter 4: Venture Builders and Scaleups.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Small business; Entrepreneurship; New business enterprises; Small Business; Entrepreneurship